The Concept of Joint Property Ownership of Husband and Wife - Musfira Musfira; Syahrizal Abbas; Khairani Khairani; Wahyu Khafidah (Universitas Serambi Mekkah, 2022)
Specifically, this study is the concept of joint property ownership of husband and wife. The focus of this study is important because, in the Marriage and Islamic Law Compilations, The property obtained in marriage becomes the joint property.So that, when a divorce or death occurs, each person gets half a share, in the regulation, there is no question about who produced it. In the reality of life in society, many wives work to earn a living, so it was interesting to study the different proportions in the distribution of property, in the event of a divorce. The problem of this research was how the concept of the joint property rights of husband and wife. In answering these problems, this research was carried out using the Socio-Legal Research method, by looking at the reality on the ground, to interpret joint property in changing situations. The technique of collecting data was through literature study, while the data analysis was qualitative. The findings of the study indicated that the practice of sharing assets with judges tends to use normative construction. Each of them got half a share and this was seen as an injustice, both through regulation and reconstruction of thinking in the distribution of the shared assets. Keywords: concept, ownership, shared property, marriage, law.